Advances in Organic Corrosion Inhibitors and Protective Coatings - Kartsonakis, Ioannis (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The interaction of metal with its environment that results in its chemical alteration is called metallic corrosion. According to the literature, corrosion is classified to two types: uniform and localized corrosion. Intervention in either in the alloy environment or in the alloy structure can provide the corrosion protection of metallic materials. Furthermore, the interference in the metal alloy environment can be conducted with the utilization of cathodic or anodic protection via the corresponding inhibitors. Therefore, the most common categorization is cathodic, anodic, and mixed-type inhibitors, taking into account which half-reaction they suppress during corrosion phenomena. The majority of the organic inhibitors are of mixed type and perform through chemisorption. In order to update the field of the corrosion protection of metal and metal alloys with the use of organic inhibitors, a Special Issue entitled "Advances in Organic Corrosion Inhibitors and Protective Coatings" is introduced. This book gathers and reviews a collection of ten contributions (nine articles and one review), from authors from Europe, Asia, and Africa, that were accepted for publication in this Special Issue of Applied Sciences.